Thickness-tunable self-assembled colloidal nanoplatelet films enable ultrathin optical gain media - Erdem, Onur (2021)
We propose and demonstrate construction of highly uniform, multilayered superstructures of CdSe/CdZnS core/shell colloidal nanoplatelets (NPLs) using liquid interface self-assembly. These NPLs are sequentially deposited onto a solid substrate into slabs having monolayer-precise thickness across tens of cm2 areas. Because of near-unity surface coverage and excellent uniformity, amplified spontaneous emission (ASE) is observed from an uncharacteristically thin film having 6 NPL layers, corresponding to a mere 42 nm thickness. Furthermore, systematic studies on optical gain of these NPL superstructures having thicknesses ranging from 6 to 15 layers revealed the gradual reduction in gain threshold with increasing number of layers, along with a continuous spectral shift of the ASE peak (∼18 nm). These observations can be explained by the change in the optical mode confinement factor with the NPL waveguide thickness and propagation wavelength. This bottom-up construction technique for thickness-tunable, three-dimensional NPL superstructures can be used for large-area device fabrication.